Identification of Morphological Characteristics and Phylogenetic Relationships of Sweet Potato (Ipomoea batatas L.) in Regency Simalungun and Regency Dairi - Mufit Musyarifah; Rosmayati Rosmayati; Revandy Damanik (Universitas Sumatera Utara, 2018)
The purpose of this research is to identification of morphological characteristic and kinship of sweet potato at Kabupaten Simalungun and Kabupaten Dairi. The research well done in regency Simalungun dan regency Dairi, North Sumatera at March to June 2017 with descriptive survey using characterzed based on International Board for Plant Genetic Resources (IBPGR) standard and purposive random sampling technique. The result of this research indicate there 21 (twenty one) genotype of sweet potato that in Kabupaten Simalungun consists of Kecamatan Silimakuta (G1, G2, G3, and G4), Purba (G5, G6 and G7), Dolok Silau (G8), Pamatang Silimahuta (G9), Dolok Perdamean (G10), Hutabayu Raja (G11) in Kabupaten Dairi consists of Kecamatan Parbuluan (G12, G13, G14, G15, and G16), Sidikalang (G17 and G18), Sumbul (G19 and G20), and Sitinjo (G21) with closest kinship is G18 and G20 with a coefecient similarity 8,541 and farthes kinship is G4 and G5with a coefecient similarity 116,338.